Control de inventarios y su incidencia en la toma de decisiones en la Despensa Don Agucho del cantón Babahoyo en el período 2022. - Vergara Briones, Ginger Noelia (2023)
Despensa Don Agucho is a retail company based in Babahoyo, Ecuador that sells essential products such as food, beverages, and tobacco. The company has gradually increased its inventory in an attempt to attract more customers, but this has led to the accumulation of products that are no longer in demand. The company has been managed empirically since its inception, and although this may have worked for a small company, it now needs to be updated in all aspects. The company lacks the necessary computer tools, so some accounting records are still handled manually, which generates untimely information and delays processes. The lack of knowledge and economic resources for internal inventory control has led to the empirical management of inventories, which can result in avoidable failures and economic losses. The problem at Despensa Don Agucho is how to improve inventory control to optimize decision-making and avoid unnecessary stockpiling, which would result in better resource management and improved profitability. Proposed measures include implementing purchasing, storage, and sales policies, adopting an inventory control system, conducting financial analysis, and implementing technological tools to improve inventory management and company profitability.